2019
DOI: 10.1111/rge.12203
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Geochemistry of Pyrite and Arsenopyrite from the Zaozigou Gold Deposit in West Qinling Orogenic Belt, Central China: Implications for Ore Genesis

Abstract: The Zaozigou gold deposit lies in the West Qinling orogenic belt, Gansu Province, China. It is one of the largest gold deposits, and the orebodies are hosted in fine‐grained slates intercalated with limestone of the Middle‐Triassic Gulangdi Formation and varied dykes. The gold orebodies are strictly controlled by the NE‐, NW‐, and SN‐trending tensional and shearing faults with high dipping angle. The mineralogy and geochemistry of pyrite and arsenopyrite are measured by electron microprobe. Pyrite has up to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For instance, the content of As in pyrite at the Zaozigou Gold Deposit (Central China) is 4.1 wt. % [37], it is 4.5 wt. % in pyrite of the Roudný deposit, Bohemian Massif [38], while As in pyrite from El Valle gold deposit (Spain) is the most abundant (up to 9.5 wt.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, the content of As in pyrite at the Zaozigou Gold Deposit (Central China) is 4.1 wt. % [37], it is 4.5 wt. % in pyrite of the Roudný deposit, Bohemian Massif [38], while As in pyrite from El Valle gold deposit (Spain) is the most abundant (up to 9.5 wt.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported that pyrite can contain visible and invisible gold (e.g., Cook and Chryssoulis, 1990; Palenik et al ., 2004; Reich et al ., 2005; Ciobanu et al ., 2012; Tang et al ., 2019). In the Xinfang gold deposit, pyrite represents the dominant Au‐bearing mineral and can be distinguished into three generations (Py1, Py2, and Py3) according to size, textures, and paragenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In arsenopyrite, arsenic and sulphur show a strong negative correlation regardless of the arsenopyrite type (Figure 15f), with a variable As/S ratio ranging from 0.72 to 0.82. The high Au contents in this low arsenic arsenopyrite (Appendix C, Table A4) are related to its non-stoichiometry [82], i.e., As concentrations between 27.52 and 29.60 at.%, compared to 33 at.% as the stoichiometric value [83]. These variations, a common feature in arsenopyrite, lead to disorder in the host lattice and allow the incorporation of gold [84].…”
Section: Correlation Of Trace Metals In Sulphidesmentioning
confidence: 93%